2012
DOI: 10.1002/adhm.201200250
|View full text |Cite
|
Sign up to set email alerts
|

Nanowell‐Trapped Charged Ligand‐Bearing Nanoparticle Surfaces: A Novel Method of Enhancing Flow‐Resistant Cell Adhesion

Abstract: Assuring cell adhesion to an underlying biomaterial surface is vital in implant device design and tissue engineering, particularly under circumstances where cells are subjected to potential detachment from overriding fluid flow. Cell-substrate adhesion is a highly regulated process involving the interplay of mechanical properties, surface topographic features, electrostatic charge, and biochemical mechanisms. At the nanoscale level the physical properties of the underlying substrate are of particular importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Ensemble arrays of nanowells with electostatically trapped charged-RGD ligand were fabricated by covalently conjugating GRGDSPK (RGD) peptide sequence onto carboxylated, fluorescent polystyrene nanoparticles, followed by selective deposition of these negatively-charged particles into the etched, positively-charged nanowells by electrostatic attraction, according to our previously described method [33] (Figure 1a). In “parallel” orientation, this 5 μm × 1 μm array was established directly along the flow within the flow channel environment (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ensemble arrays of nanowells with electostatically trapped charged-RGD ligand were fabricated by covalently conjugating GRGDSPK (RGD) peptide sequence onto carboxylated, fluorescent polystyrene nanoparticles, followed by selective deposition of these negatively-charged particles into the etched, positively-charged nanowells by electrostatic attraction, according to our previously described method [33] (Figure 1a). In “parallel” orientation, this 5 μm × 1 μm array was established directly along the flow within the flow channel environment (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…While the benefits of linear ridge-and-groove patterning and the RGD-nanoparticle array appear to be similar, RGD-nanoparticles provide the additional benefit of post-fabrication control over the spatial characteristics of the surface. Previous work with this array has indicated that nanowells unbound to RGD-nanoparticles do not bear the same cell adhesive benefits of the full RGD-nanoparticle array [33]. Therefore, through control of RGD-nanoparticle deposition, an further control over cell adhesion may be added.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations